EFFECTIVENESS PROGRAM PKH IN IMPROVING THE WELFARE OF THE COMMUNITY IN TIWUGALIH VILLAGE SUBDISTRICT PRAY - Baehaqi Baehaqi (Jurnal Ekonomi, 2022)
The purpose of this study is to find out how effective the Family Hope Program (PKH) is in improving community welfare in Tiwugalih Village, Praya District. The research method used is qualitative research with a narrative approach. The results of this study indicate that. The Family Hope Program (PKH) in Tiwugalih Village has been implemented effectively based on indicators of the accuracy of the objectives, the accuracy of the implementation process, and the benefits felt by PKH Beneficiary Families (KPM). The Family Hope Program (PKH) in the Tiwugalih District has not been implemented effectively, as seen from the indicators of ineffective targeting because there are still many poor people in Tiwugalih Village who should be included in the KPM but cannot receive the assistance program because they are not registered in the Integrated Social Welfare Data (DTKS) from the Ministry of Social Affairs, while there are also those who should not be eligible to receive the assistance program but instead receive the program. In addition, the monitoring activities carried out have not been carried out optimally due to obstacles in the field. Regarding the effectiveness of the PKH program in improving the welfare of the community, this program has not been very effective in improving the welfare of the PKH recipients because the funds they receive are not so large.